TRANSACTION COSTS: A LEGENDARY THEORY OF THE FIRM - Hasanah, Nur (Journal of Business Studies and Management Review, 2024)
There are three widely recognized perspectives on the organizations. They are resource dependence, efficiency, and population perspectives. The purpose of this paper is to explain the history of transaction cost theory, the theory of the firm, the nature of the firm, the transaction cost economics, and the critiques for this theory. Articles in leading journals listed in EBSCO, Emerald, JSTOR, ProQuest, and ScienceDirect databases were chosen. A conceptual and relational analysis was conducted to fulfill the purpose of this paper. Results show that an acceptable theory of the firm should possess the capability to elucidate not just the reasons for the existence of firms in a market economy, but also other aspects. At the very least, it should have the capacity to clearly define and articulate the limits of a firm’s activities, including what tasks are performed internally and what tasks are outsourced or delegated to others, as well as how these activities are structured and how the firm achieves growth and success. While profit-oriented organizations have long recognized the numerous advantages of inter-organizational collaboration, non-profit organizations are now beginning to understand some of these benefits, including cost savings through shared administrative expenses, enhanced value propositions, increased efficiency, strengthened programs, utilization of compatible skills and abilities, and improved leadership skills.